ANALISIS POLA MINAT KONSUMEN DENGAN ALGORITMA APRIORI - Sugeng Ariyadi, Faisal Nuryawan; Mailoa, Evangs (UNIVERSITAS STEKOM, 2024)
Gunthem Coffee is a cafe located in Semarang as well as a foodtruck when there is an event. Gunthem Coffee provides 20 coffee menus. The large number of coffee menus that spoil consumers, Gunthem Coffee decided to make policies for marketing strategies. Based on the problems experienced by Gunthem Coffee, it is necessary to conduct research on consumer interest patterns so that it will benefit both Gunthem Coffee and consumers. This research uses the a priori algorithm based on field data that can be calculated objectively. The results obtained from the apriori algorithm calculation are to get two (2) association rules with a minimum support of 30% and a minimum confidence of 60%, namely if you buy Black Pink, you will buy Kopi Susu Sanger with a support value of 50% and a confidence value of 67% and if you buy Sanger Milk Coffee, you will buy Black Pink with a support value of 50% and a confidence value of 87%.